MANAGEMENT OF ECONOMIC SECURITY OF AN ENTERPRISE IN THE CONDITIONS OF CIRCULAR ECONOMY (Development Service Industry Management, 2025)
In the article, the authors analyze the genesis of the concept of “economic security of an enterprise”. Initially, it was determined that, along with the key characteristics of this term (threat protection; stability and resilience; efficient use of resources; social responsibility; partnership, harmonization of interests with the external environment; adaptation to changes and economic freedom), it is important to focus on smart, sustainable and inclusive business growth. Indeed, taking into account the principles of the circular economy in all elements of the economic security of the enterprise ensures the sustainability, competitiveness and long-term stability of the enterprise, harmonizing its economic interests with the environmental and social needs of society. The authors define economic security of an enterprise as a state of protection of an enterprise from internal and external threats, which ensures achievement of competitive advantages and sustainable development based on innovative approaches to implementation of cyclic models of resource use, harmonization of interests of all stakeholders and preservation of a sufficient degree of economic freedom to adapt to changing environmental conditions.  By enterprise economic security management, the authors mean a set of measures, processes and tools aimed at forecasting, identifying, assessing and forming a unique ability to counter internal and external threats, which ensures sustainable development of an enterprise.
Keywords: economic security of an enterprise; management; circular economy; sustainable development